Contemporary Wooden Watercraft of the Zanzibar Channel, Tanzania: Type and Technology, Continuity and Innovation. (3rd July 2021) - Cooper, John P.; Blue, Lucy; Ghidoni, Alessandro; Ichumbaki, Elgidius B.
ABSTRACT: This article documents and presents the range of wooden fishing and cargo-carrying watercraft in use in the contemporary Zanzibar Channel, Tanzania. The work is based on surveys conducted in 2018 on Unguja, the principal island of the Zanzibar archipelago, and in 2019–2020 in Bagamoyo, mainland Tanzania, and its immediate environs. The authors present a broad typology of the principal wooden vessel types in the form of 3D photogrammetric models, orthographic views, and photographs. The principal construction features and uses of each type are presented and the state of play of contemporary wooden-boat construction in this part of East Africa discussed.